INFORMATIОN COMPETENCE AS A STRUCTURAL COMPONENT OF THE PROFESSIONAL PEDAGOGICAL COMMUNICATIVE COMPETENCE OF A TEACHER IN THE CONTEMPORARY EDUCATIONAL SPACE - Kohut, Iryna (Educological discourse, 2018)
Text of the abstract – the concept of information competence, professional-pedagogical communicative competence in the future teacher is considered. The structure of vocational and pedagogical communicative competence of the future teacher is characterized, the specifics of the communicative activity of the teacher are grounded. Specifies the functions and conditions under which the teachers’ professional and pedagogical communication is carried out. The important component of the teacher’s professional and pedagogical communicative competence in the educational environment is outlined - information competence.